Kustannustehokkaita työkaluja totuuden hämärtämiseen - Talvitie, Vesa (Tieteessä tapahtuu, 2021)
Ronald E. Purser: McMindfulness. How mindfulness became the new capitalist spirituality. Repeater 2019. Edgar Cabanas ja Eva Illouz: Manufacturing happy citizens. How the science and industry of happiness control our lives. Polity Press 2018.